Approaching mythology in the history curriculum of compulsory education in Greece. Issue 2 (17th October 2019) - Vlachaki, Maria; Kokkinos, George; Papandreou, Zeta
Myth can be a first step in historicizing the past and at the same time in appreciating ancient cultures and developing the essential skill of empathy. A main objective of the history curriculum for the third grade of primary school in Greece is for children at 8 and 9 years old to familiarize themselves with the basic cultural elements of the origins of Greek, European and global civilization. Ancient Greek myths are taught using references and links to the myths of other peoples and cultures, and by identifying similarities and differences in the interpretation of the world within the framework of a multi-perspective, intercultural approach. Myths also depict the relationship between man and nature. They constitute man's attempt to interpret the physical and social environment. In addition, myths present the relationship between man and the divine in the early stages of cultural evolution, and at the same time provide evidence of the culture of a historical period. Pupils become aware of the fact that myths used to have a symbolic and ritualistic function, which aimed to initiate younger members into the acceptable practices and values of their community. Myths provided meaningful models of action (exempla) through their allegorical nature. Moreover, myths facilitate the analysis of human behaviour by introducing the schema of cause and effect. Mythical thought seeks to understand causality, which is also the primary aim of science. In this sense, mythical discourse is connected to scientific discourse. Within the framework of a methodological approach based on these theoretical assumptions, this paper also includes a presentation of educational activities and pupils' perceptions as part of a survey conducted in a third-grade primary school class in Greece.